2006
DOI: 10.1108/13612020610679268
|View full text |Cite
|
Sign up to set email alerts
|

Supplier management in fast moving fashion retailing

Abstract: Purpose -The over-arching purpose of this research is to explore the issue of supplier management within the context of fast-moving fashion retailing. Design/methodology/approach -Qualitative research utilising key informant interviews was used.Findings -The research suggests that retailers may adopt a multi-tiered approach, whereby dynamism and responsiveness are achieved through only partially agile supply chains. Practical implications -Based on the nature of the qualitative data, the paper provides useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 18 publications
0
48
0
2
Order By: Relevance
“…The changing dynamics of the fashion industry over this period, such as the fading of mass production, increase in number of fashion seasons, and modified structural characteristics in the supply chain (Doyle et al, 2006;Fernie et al, 2009;Bhardwaj and Fairhusrst, 2010) have forced retailers to desire low cost and flexibility in design, quality, delivery and speed to market (Doyle et al, 2006). Nevertheless, there exist also high-cost supply markets like Italy and Spain that have a significant number of manufacturing suppliers (Fernie et al, 2009).…”
Section: The Clothing Retailers In the International Contextmentioning
confidence: 99%
“…The changing dynamics of the fashion industry over this period, such as the fading of mass production, increase in number of fashion seasons, and modified structural characteristics in the supply chain (Doyle et al, 2006;Fernie et al, 2009;Bhardwaj and Fairhusrst, 2010) have forced retailers to desire low cost and flexibility in design, quality, delivery and speed to market (Doyle et al, 2006). Nevertheless, there exist also high-cost supply markets like Italy and Spain that have a significant number of manufacturing suppliers (Fernie et al, 2009).…”
Section: The Clothing Retailers In the International Contextmentioning
confidence: 99%
“…Indeed, a study by Forker and Stannack (2000) revealed that buyer-supplier relationships based on cooperation may be less effective than those forged through competition. As retailing becomes more fast fashion in orientation, the primary criterion for buyers in selecting a supplier is not necessarily price, due to intense market competition and the requirement of just-in-time deliveries (Doyle et al 2006). This shift was made evident by Lowson's (2001) study that revealed how hidden costs can outweigh the benefits of buyer relationships with suppliers in low-cost countries, and particularly those costs that emerge from engaging in long distance sourcing relationships.…”
Section: Elements Of the Buyer-supplier Relationshipmentioning
confidence: 99%
“…Young et al (2003: 444) define flexibility as: "the willingness of parties in a trading relationship to adapt, change, or adjust to new knowledge without resorting to a series of new contracts and renegotiations." This flexibility is particularly important within the fast fashion supply chain (Doyle et al 2006). Ultimately, the supplier's ability to respond with flexibility leads to the viability of long-term relationships with buyers (Webb and Laborde 2005).…”
Section: Elements Of the Buyer-supplier Relationshipmentioning
confidence: 99%
“…Although retailers may source from hundreds or thousands of suppliers worldwide to maximise flexibility, a significant proportion of business tends to be channelled through a smaller number of key suppliers. Teller et al (2016) noted the importance of key supplier relationships in SCM, as they allow firms to achieve the advantages of responsiveness, agility, speed and ultimately profitability (Doyle et al, 2006).…”
Section: Fashion Supply Chain Managementmentioning
confidence: 99%